Women for science and science for women: Gaps, challenges and opportunities towards optimizing pre-exposure prophylaxis for HIV-1 prevention - Karim, Quarraisha Abdool; Archary, Derseree; Barré-Sinoussi, Françoise; Broliden, Kristina; Cabrera, Cecilia; Chiodi, Francesca; Fidler, Sarah J.; Gengiah, Tanuja N.; Herrera, Carolina; Kharsany, Ayesha B. M.; Liebenberg, Lenine J. P.; Mahomed, Sharana; et al. (Frontiers in Immunology, 2022)
In the era of oral pre-exposure prophylaxis (PrEP), increasing rates of new HIV-1 infections are observed worldwide which continue to disproportionally affect girls and young women. However, the majority of early phase HIV-1 clinical trials disproportionally enroll men. The efficacy of topical and systemic prevention strategies is highly dependent of physiological and social factors which are gender specific. Here we review the past and current developments of HIV-1 prophylaxis options for women with special focus on PrEP considering the diverse factors that can hinder their efficacy. Furthermore, we highlight how female scientists, clinicians, and community advocates should be well represented to further improve development in the field.